Nutritional composition and fatty acid profile of Yellowfin Tuna (Thunnus albacares) by-products in Sri Lanka - Dilini Jayaweeraa, D.; Dargentolleb, C.; Kuganathanc, S. (University of Jaffna, 2024)
The present study evaluated the nutritional composition and fatty acid profile of juvenile yellowfin tuna (n = 12, mean weight = 0.875 ± 0. 107 kg) heads, dorsal skins, and caudal muscles with fins. Fatty acid methyl esters (FAME) were separated by gas chromatography (Varian 3900 GC). The highest protein content was obtained in the caudal muscles with fins (23.80 ± 0.14 %) and the lowest (18.75 ± 0.21 %) as reported in the yellowfin tuna head. The highest moisture content was recorded in the caudal muscles with fins (77.06 ± 0.31%). The ash content was comparatively higher (8.65 ± 0.78%) in yellowfin tuna heads than in the dorsal and caudal muscles. The highest fat content was recorded in yellowfin tuna heads (4.18 ± 0.33%) which could be a potential source for fish oil extraction. The most abundant fatty acids in by-products were identified as docosahexaenoic poly-unsaturated fatty acid (DHA/PUFA) (head: 26.63 ± 0.19%, dorsal: 34.71 ± 0.72%, caudal: 31.27 ± 0.90%), followed by saturated fatty acids; palmitic acid (SFA) (head: 22.52 ± 0.22%, dorsal: 20.14 ± 0.47%, caudal: 20.72 ± 0.20%). The results of the present study indicate that omega-3 PUFAs ranged from 35.12% to 42.93% and were higher than omega-6 PUFAs ranging from 4.15% to 4.74% in yellowfin tuna heads, dorsal skin, and caudal muscles. The nutritional composition and fatty acid profile revealed that the yellowfin tuna by-products are excellent sources for extracting omega-3 fatty acids and protein for the food and pharmaceutical industries in Sri Lanka.
Keywords: By-products; Fatty acid profile; Nutritional composition; Protein; PUFA